Determination of restrictive economic functions and evolution tendencies of technical indicators from agriculture in the North-West region - Vili Dragomir; Nela Dragomir (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
In the knowledge process we have a variety of methods, ways, means enabling the identification, scientific determination of the phenomena from nature and society. A current widely used model is modeling the investigated phenomena. Research methods used in order to elucidate economic processes and evolution trends of plant and animal systems in territorial profile were: regression function method - which statistically expresses how characteristic result y changes due to changes of characteristic x factor for in the case that the variance of y would only be based on the variation of x; the method of least squares - through which is obtained a solution of an over determined system of equations, which has more equations than unknowns. The least square means that the obtained solution minimizes the sum of squares of deviations from the values equations. Indicators calculated very useful in assessing the development prospects of the North-West region, were based on two assumptions: a) the development trend will remain the same, in this case putting only the problem is if development rate of the phenomena will be the same or changes to the new conditions; b) assumes that changes the trend and development rate
Keywords: 330; modeling; assumptions; data series